Menggali Nilai Pendidikan Karakter dalam Cerita Rakyat Punden: Kajian Sastra Lisan di Kecamatan Dukun, Kabupaten Gresik - Muttaqin, Khoirul; Murniatie, Itznaniyah Umie; Lailiyah, Fitrotul (Universitas Tidar, 2025)
This study examines the character education values contained in the Punden folklore of Dukun Subdistrict, Gresik Regency, aiming to uncover the potential of folklore as a medium for character education. The objects of the study are five Punden stories from the western, central, and eastern regions of the subdistrict. The research employs a qualitative descriptive method, specifically ethnographic research. The ethnographic approach is used to understand the values embedded in the five Punden stories, collected through interviews, recordings, and note-taking. The informants were determined using snowball sampling, and data validation was conducted through theory triangulation. Data analysis utilized descriptive and content analysis techniques. The findings reveal that the Punden stories are rich in character values based on religion, Pancasila, culture, and national education goals, with only three values—patriotism, environmental care, and love for reading—not identified. The emerging values include religiousness, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, nationalism, appreciation of achievements, communicativeness, love of peace, social care, and responsibility. The results indicate that Punden folklore can serve as an effective means to develop students' character. The discussion highlights the importance of these values in character education and their potential as teaching materials. Therefore, it is recommended that the Punden stories from Dukun Subdistrict be utilized as teaching materials, with the development of appropriate teaching modules. The conclusion asserts that Punden folklore holds significant relevance for character education, supports the preservation of local culture, and suggests its inclusion in the educational curriculum.